Analysis and Design of it Service Users in Problem Management and Inci-dent Management in Hospitals - Ali Imron; Zena Lusi; Putri Intan Avita; Fahri Rahman (Law and Economics, 2026)
Utilization of Information Technology (IT) in the healthcare sector plays a vital role in improving service quality, operational effectiveness, and patient satisfaction. The Banyuasin Regional Hospital (RSD Banyuasin) faces challenges in managing incidents and IT service-related problems that may disrupt both medical and administrative services. This study aims to analyze and design IT service governance processes for Incident Management and Problem Management based on the ITIL V4 framework. The research method involves observations, interviews, and analysis of supporting documents to identify the current conditions, user needs, and gaps through a gap analysis against ITIL best practices. The analysis results indicate that incident handling processes are not systematically documented and lack a structured escalation mechanism, while problem management remains reactive without proper root cause documentation. Based on these findings, an IT service design model was developed that integrates the workflows of Incident Management and Problem Management in accordance with ITIL V4 principles, including identification, recording, classification, escalation, and continuous improvement. This design is expected to enhance the responsiveness of incident handling, reduce the recurrence of problems, and support the continuity of IT services at RSD Banyuasin